MP‐AzeFlu is more effective than fluticasone propionate for the treatment of allergic rhinitis in children. Issue 8 (1st June 2016) - Berger, W.; Bousquet, J.; Fox, A. T.; Just, J.; Muraro, A.; Nieto, A.; Valovirta, E.; Wickman, M.; Wahn, U.
Abstract: The objective was to evaluate the efficacy of MP‐AzeFlu (Dymista ® ) vs fluticasone propionate (FP), (both 1 spray/nostril bid), in children with allergic rhinitis (AR). MP‐AzeFlu combines azelastine hydrochloride, FP and a novel formulation in a single spray. Children were randomized in a 3 : 1 ratio to MP‐AzeFlu or FP in this open‐label, 3‐month study. Efficacy was assessed in children aged ≥ 6 to <12 years (MP‐AzeFlu: n = 264; FP: n = 89), using a 4‐point symptom severity rating scale from 0 to 3 (0 = no symptoms; 3 = severe symptoms). Over the 3‐month period, MP‐AzeFlu‐treated children experienced significantly greater symptom relief than FP‐treated children (Diff: −0.14; 95% CI: −0.28, −0.01; P = 0.04), noted from the first day (particularly the first 7 days) and sustained for 90 days. More MP‐AzeFlu children achieved symptom‐free or mild symptom severity status, and did so up to 16 days faster than FP. MP‐AzeFlu provides significantly greater, more rapid and clinically relevant symptom relief than FP in children with AR.